Hubungan Intensitas Pencahayaan dan Penataan Kamar dengan Tingkat Konsentrasi Belajar di Rumah Kos Putri Kajor, Nogotirto, Gamping, Sleman, Yogyakarta - Fwbi Hadiyani; Tuntas Bagyono; F.X. Amanto Rahardjo (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Boarding houses rent rooms for temporary stays. For students who living far from parents these places are their second home because almost of their activities are carried out in the room, included studying which needs high concentration. Based on the preliminary survey held in the female boarding houses located behind the Polytechnic of Health of Yogyakarta, it was found that the average measurement of light intesity was 24,81 lux and most rooms had unsuited room arrangement. The purpose of this study was to determine the relationship between light intensityand room arrangement and the level of studying concentration among the Female Boarding House of Kajor, by conducting a cross sectional approached survey. There were 60 boarding rooms under the study with 60 students occupant who were selected purposively as the respondents. The light intensity was measured by lux meter, the room arrangement was assessed by a check list and the studying concentration was identified by using a questionnaire. The results show that only 46,7% rooms had adequate light intensity, only 48,3% rooms had suited room arrangement, and respondents who had bad concentration outnumbered those who had the good ones.Data analysis with using Spearman rank correlation test at 5% significance level, concludes that both light intensity and room arrangement are significantly have high and positive correlations with studying concentration, i.e. the corresponding ? coefficients were 0,991 and 0,951, respectively, and the all p-values were below 0,001.